Numerical modeling of nickel-infiltrated gadolinium-doped ceria electrodes reconstructed with focused ion beam tomography. (1st February 2016) - Kishimoto, Masashi; Lomberg, Marina; Ruiz-Trejo, Enrique; Brandon, Nigel P
Graphical abstract: Highlights: A 1D numerical model of Ni-GDC electrodes is developed. Microstructure of a nickel-infiltrated GDC electrode is obtained using FIB-SEM. Overpotential characteristics are successfully reproduced by the developed model. Sensitivity analysis reveals microstructure-performance relationships. The developed model offers guidelines to optimize electrode microstructures. Abstract: A one-dimensional numerical model of a nickel-infiltrated gadolinium-doped ceria (Ni-GDC) electrode has been developed to investigate the effects of electrode microstructure on performance. Electrode microstructural information was obtained with focused ion beam tomography and microstructural parameters were quantified, such as tortuosity factor, surface area and particle/pore sizes. These have been used to estimate the effective transport coefficients and the electrochemical reaction rate in the electrodes. GDC was considered as a mixed ionic and electronic conductor and hence the electrochemical reaction is assumed to occur on the GDC-pore contact surface, i.e. double-phase boundaries (DPBs). Sensitivity analysis was conducted to investigate the effect of electrode microstructure on both transport properties and electrochemical activity, including the effect of DPB density, GDC tortuosity factor and pore size. The developed model offers a basis to understand the microstructure-performance relationships and to further optimize the electrode microstructures.